The Number of Colon Crypts in Digital Mucosal Samples: A New Independent Parameter for Diagnosing Ulcerative Colitis - Rubio, Carlos A.; Lang-Schwarz, Corinna; Matek, Christian; Kamaradova, Katerina; Vieth, Michael (Cancer Diagnosis & Prognosis, 2023)
Background/Aim: It has been demonstrated that most routine biopsies from the colon and rectum display cross-cut crypts (CCC). The aim was to assess the number of CCC in microscopic isometric digital samples (0.500 mm2) from routine colon biopsies. Patients and Methods: Colon biopsies from 224 patients were investigated: 99 in patients with ulcerative colitis (UC), 31 UC in remission (UCR), 28 infectious colitis (IC), 7 resolved IC (RIC), 19 diverticular sigmoiditis (DS), and 40 normal colon mucosa (NCM). Results: A total of 8,024 CCC were registered: 2,860 (35.6%) in UC, 1,319 UCR (16.4%), 849 (10.6%) in IC, 340 (4.2%) in RIC, 795 (9.9%) in DS, and 1,861 (23.2%) in NCM. The CCC frequencies in UC and IC were significantly lower (p<0.05) than those in UCR, RIC, DS, and NCM. Conclusion: By the simple algorithm of counting CCC in standardized isometric microscopic digital circles measuring 0.500 mm2, it was possible to differentiate between UC (long-lasting inflammation) and IC (short-lasting inflammation) on the one hand, and UCR, RIC, DS (persistent inflammation), and NCM, on the other. The counting of CCC in the algorithm by five pathologists working in three disparate European Countries, was found to be reproducible.<br
Keywords: ulcerative colitis; colon crypts; frequency; digital samples